Evaluasi Model Context, Input, Process, Product (CIPP) Pada Program Unggulan Riset MAN 3 Palembang - nurviana nurviana (Institut Agama Islam Sahid (INAIS) Bogor, 2023)
The aim of the study was to analyze the extent to which effectiveness is usability, as well as to analyze the inhibiting and supporting factors in the implementation of the MAN 3 Palembang Research Excellence Program using the Context, Input, Process, Product (CIPP) approach model from Daniel L. Stufflebeam. This type of research is field research using data analysis and a qualitative approach. Data collection techniques used include: observation, interviews and documentation. The data analysis technique used is to carry out qualitative data analysis continuously until it is complete and the data is saturated. The stages carried out by the researcher were data reduction, data presentation and conclusion and verification. The results of this study indicate that in Context Evaluation, what is done after the program is running is that the program has reached the evaluation stage by carrying out program improvements by the MAN 3 Palembang management team. Input evaluation, supervision and assessment of KIR supervisor teachers and students has been carried out as well as during the selection of supervisor teachers and students. Materials, training, methods, media, research program facilities and infrastructure, operational funding sources and incentives have been managed as well as possible. Process Evaluation, MAN 3 Palembang has carried out a superior research program in the form of implementing both intra-curricular and extra-curricular Youth Scientific Groups (KIR). What makes it possible to revise the decision is that students who are advised that research class students whose proposals do not pass the selection for the competition to remain in the research class for the following year, are not immediately transferred to the regular class. Product, and achievement in winning research competitions, namely KIR's competition achievements are already good, while the research culture needs to be improved again. The inhibiting factor is that it is still possible to experience internet network interference, not all students use laptops, a lack of understanding of some students, lack of communication, students who still do not understand the material. Supporting factors are support in the form of motivation from various related parties, complete facilities and infrastructure, competent educators, enthusiastic students, support from student guardians and committees, comfortable school environment